Hydropericardium syndrome caused by fowl adenovirus serotype 4 in replacement pullets - LIN, Su; SHI, Shaohua; ZHU, Chunhua; CHEN, Zhen; CHEN, Cuiteng; HUANG, Yu; QI, Baoming (Journal of Veterinary Medical Science, 2019)
Hydropericardium syndrome (HPS) is one of the important emerging diseases causing huge losses to the poultry industry. It affects mainly 3- to 6-week-old broiler chickens and rarely occurs in breeding and laying flocks. Recently, an HPS case was recorded with a sudden heavy mortality in a 100-day-old laying flock. A fowl adenovirus serotype 4 (FAdV-4), named as GDMZ strain, was isolated and identified using polymerase chain reaction coupled with electron microscopy. The animal experiment showed that a mortality of 100% was recorded with hydropericardium as a conspicuous lesion throughout the course of infection. Microscopically, vacuolar changes and intranuclear inclusion bodies were observed in the liver and vacuolar changes were observed in the heart. The complete genome sequence of GDMZ strain was determined to investigate the molecular properties of GDMZ strain. The comparative analysis revealed that the novel Chinese FAdV-4 isolate contained open reading frame (ORF) 19, ORF27, and ORF48 genomic deletions. The phylogenetic analysis revealed that FAdV-4 could be divided into two major clades, of which Chinese FAdV-4 were located at a distinct clade.